LA SHOAH, LE MAL ET LA PHILOSOPHIE - Gérard BENSUSSAN (Studia Universitatis Babeș-Bolyai. Philosophia)
Shoah, Evil and Philosophy. To speak of the philosophy of the Shoah presupposes a philosophy of philosophy -that would stand in the pre- or post-position of a meaning and the subsumption of an object under a concept. But there is no concept of the Shoah because there is no intelligibility that could justify it. Of this «incomprehensible incontestable» as Victor Hugo said of God, literature can only approach the massive enigma. The «banality of Evil» prevents one from thinking that Evil thinks, and with such a radicality that it demands of the existence itself, and a fortiori of that of the Shoah, irrefutable proofs. By blurring the hypothesis of a flawless equivalence of intelligibility and existence, the Shoah questions the question of meaning.